The place and role of police education in ensuring the implementation of the functional purpose of the national police based on foreign experience - Sofina, I. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
The article is devoted to determining the role and place of police education in ensuring the implementation of the functional purpose of the National Police, based on foreign experience; as well as substantiating the need to reform the functioning, management and efficiency of the administrative apparatus of the National Police of Ukraine. The article examines the main aspects of international cooperation in the field of training of National Police employees. The issue of improving the qualifications of senior managers of the National Police using the experience of European Union countries is revealed. The importance of informing the heads of bodies and units of the National Police of Ukraine about the essence and importance of international norms on the protection of human rights and the peculiarities of the activities of various international law enforcement organizations in these processes is determined. The peculiarities of the application of international cooperation in improving the system of administrative and legal support for the professional training of the management of the National Police of Ukraine are investigated. The usefulness of the positional identity of the functional purpose of the National Police of Ukraine with the police bodies of the European Union countries is emphasized as a means of eliminating the problem of divergence between European political systems, legislation and education, which creates obstacles to the development of cooperation. The current problems of international cooperation in the field of training police managers in the context of modern realities of administrative and legal development are highlighted. Important methods of international cooperation are presented to improve the functional purpose of the police, such as the inclusion of educational institutions of Ukraine in programs implemented by international organizations and the coordination of research on law enforcement activities conducted with the support of international organizations on the territory of Ukraine, etc.